Increased cardiovascular risk in patients with fibromyalgia: An integrative review of the literature (Research, Society and Development, 2024)
Introduction: Fibromyalgia is a chronic pain syndrome that affects approximately 5% of the world's population. In addition to the physical and mental impact, fibromyalgia may be associated with an increased cardiovascular risk in these patients. Objective: To evaluate the association between increased cardiovascular risk in patients with fibromyalgia. Methodology: This is an integrative review of the literature, carried out in May 2024, with data collected from the Virtual Health Library. In total, 18 articles were found, of which 4 (n = 4) were selected to compose this study. Results: It was observed that patients with fibromyalgia may have a higher cardiovascular risk when compared to patients without fibromyalgia. The mechanisms that lead to this susceptibility are diverse, such as increased interleukin 6, metabolic and inflammatory changes and increased thrombogenic predisposition. As a result, cardiovascular complications, such as coronary disease, stroke, transient ischemic attack, end up increasing in patients with fibromyalgia, especially in those individuals in whom fibromyalgia is associated with other cardiovascular risk factors. Conclusion: It is important to reinforce knowledge about this association, in order to expand prevention and health education for patients with fibromyalgia. Furthermore, a better understanding of this association broadens the perspective in relation to the systemic outcomes caused by fibromyalgia, which go beyond its classic pain condition.